How many non-negative integer solutions of the equation a + 4 b + c + 3 d + 3 e + 3 f + 6 g + 6 h = 2 0 are also the solutions of j + 2 k + l + 3 m + n + x + p + 6 q = 2 0
Details and assumptions :-
∙ Solutions here means the ordered 8-tuples ( a , b , c , d , e , f , g , h ) for the first equation and ( j , k , l , m , n , x , p , q ) for the second equation.
∙ Are also solutions of means the 8-tuple (a,b,c,d,e,f,g,h) which satisfies 1st equation, must also satisfy the 2nd equation.
(If a 0 , b 0 , c 0 , d 0 , e 0 , f 0 , g 0 , h 0 ) is some solution tuple of 1st equation, then j = a 0 , k = b 0 , l = c 0 , m = d 0 , n = e 0 , x = f 0 , p = g 0 , q = h 0 must satisfy second equation.
∙ a , b , c , d , e , f , g , h , j , k , l , m , n , x , p , q ∈ N ∪ {0}. (All non-negative integers).
Problem 1 of this type was a bit easier, and it gives hint for this one.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yep. Exactly the same!
Is there a way to do this without generating functions?
A way without generating functions (casework wink wink)
We subtract the two equations to get 2b+2e+2f+5g=0.
Therefore, b=e=f=g=0.
Now we must solve the equation a+c+3d+6h=20.
We do casework on 6h (not that bad since there are only 4 cases).
Case 1: 6h=18.
Then, a+c+3d=2 which there are only 2 solutions for (d=0).
Case 2: 6h=12.
subcasework on 3d.
When 3d=6, there are 3 solutions.
3d=3, 6 solutions.
3d=0, 9 solutions.
3+6+9=18 for this case.
Case 3: 6h=6
Similarly, 3+6+9+12+15=45.
Case 4: 6h=0
3+6+9+12+15+18+21=84.
We add up all of these to get 3 + 1 8 + 4 5 + 8 4 = 1 5 0
Although the usual method is the one using generating functions, I loved this casework.
Problem Loading...
Note Loading...
Set Loading...
Just like the method in previous problem, we can say that for common solutions, the variables j , k , l , m , n , o , p , q can be replaced by a , b , c , d , e , f , g , h respectively.
This transforms the equations into a + 4 b + c + 3 d + 3 e + 3 f + 6 g + 6 h = 2 0 . . . . . . . . . . . . . . . . . ( i ) a + 2 b + c + 3 d + e + f + g + 6 h = 2 0 . . . . . . . . . . . . . . . . . ( i i )
Subtract (ii) from (i), then we get
2 b + 2 e + 2 f + 5 g = 0
As we want non-negative integer solutions, b = e = f = g = 0 .
Hence we just want solutions to the equation
a + c + 3 d + 6 h = 2 0
(See that the variables whose co-efficient corresponding to the variable in 2nd equation is same , for them only the values will be non-zero)
So, this is same as finding non-negative integer solutions to the equation a + c + d ′ + h ′ = 2 0 , with the condition d ′ is multiple of 3 and h ′ is multiple of 6 .
This will have the generating function for a as k = 0 ∑ 2 0 x k
Generating function for c as k = 0 ∑ 2 0 x k
Generating function for d ′ as k = 0 ∑ 6 x 3 k
Generating function for h ′ as k = 0 ∑ 3 x 6 k
Thus, the generating function for our sum, to be 20, it'll be the co-efficient of x 2 0 in the function
( k = 0 ∑ 2 0 x k ) 2 ( k = 0 ∑ 6 x 3 k ) ( k = 0 ∑ 3 x 6 k )
And it is 1 5 0